2000
DOI: 10.1002/(sici)1096-9896(200004)190:5<619::aid-path555>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein 1, interleukin 8, and chronic airways inflammation in COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the most common causes of death, with cigarette smoking among the main risk factors. Hallmarks of COPD include chronic air¯ow obstruction and chronic in¯ammation in the airway walls or alveolar septa. An earlier study reported elevated numbers of macrophages and mast cells within the bronchiolar epithelium in smokers with COPD, compared with smokers without. Since speci®c chemokines may be involved in this in¯ux, the in situ protein and mRNA expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
0
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(176 citation statements)
references
References 32 publications
(55 reference statements)
7
160
0
8
Order By: Relevance
“…Staining intensities for EMMPRIN, MMP-2, MMP-7 and MMP-9 expression were then scored for each cell type at the same magnification using a visual scoring method with grades ranging from 0 to 3 (0 = no staining; 1 = moderate staining; 2 = intense staining; 3 = very intense staining), as previously described (20). We evaluated co-localization of EMMPRIN with MMPs on serial sections from the same tissue block.…”
Section: Semi-quantification Of Immunohistochemistrymentioning
confidence: 57%
“…Staining intensities for EMMPRIN, MMP-2, MMP-7 and MMP-9 expression were then scored for each cell type at the same magnification using a visual scoring method with grades ranging from 0 to 3 (0 = no staining; 1 = moderate staining; 2 = intense staining; 3 = very intense staining), as previously described (20). We evaluated co-localization of EMMPRIN with MMPs on serial sections from the same tissue block.…”
Section: Semi-quantification Of Immunohistochemistrymentioning
confidence: 57%
“…IL-8 and MCP-1, which are chemotactic factors for monocytes and neutrophils, respectively, produced mainly by vascular endothelial cells of the lungs, 18,19 are thought to be involved in the development of acute lung injury and inflammation. [20][21][22][23] The levels of IL-8 and MCP-1 in bronchoalveolar lavage fluid have been reported to correlate with clinical severity and mortality in patients with acute lung injury. 23 Regarding the pathogenesis of RPE, the pulmonary microvascular endothelium is mechanically destroyed immediately after the collapsed lung has been expanded, and ischemia-reperfusion injury subsequently occurs in the injured pulmonary microvessels.…”
Section: Discussionmentioning
confidence: 93%
“…However, monocytes/macrophages are the major source of CCL2 (27). In line with this cellular pattern of CCL2 expression, De Boer et al reported a strong signal for CCL2 in macrophages and a weak signal in alveolar epithelial cells (13).…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 (MCP-1; monocyte chemoattractant protein-1) is produced by many cell types, including fibroblasts, endothelial, epithelial, smooth muscle, mesangial, astrocytic, monocytic and microglial cells. It has been shown to be elevated in tissue sections in ex-smokers with, as compared to exsmokers without, COPD (13). CCL7, previously called MCP-3 (monocyte chemoattractant protein-3), has an expression pattern that is more restricted compared with CCL2.…”
Section: Chemokine Expression By Small Sputum Macrophages In Copdmentioning
confidence: 99%